Dari Konsumerisme Ke Produktivitas: Pastoral Konseling dalam Menghadapi Tantangan Gaya Hidup Pekerja Ritel di Kota Manado - Dendeng, Leonardo Caesar; Salindeho, Veibe; Horohiung, Debora Natalia; Takasihaeng, Meivi Lestari Putri (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2025)
This study investigates the phenomenon of consumerism and its impacat on the productivity of Generation Z retail workers in Manado city. The widespread consumerism has affected the mental well-being and work motivation of these workers, leading of stress and dissatisfaction. Utilizing a qualitative approach, data were collected therough in-depth interviews and participatory observations, and analyzed using thematic analysis. The finding indicate that counseling pastoral can assist retail workers in managing social pressures and shifting their mindset from excessive consumption to more meaningful productivity. This highlights the importance of emotional and spiritual support for retail workers to enhance their quality of life and performance.